Madame Curie - Curie, Eve, 1904-2007.; Sheean, Vincent, 1899-1975. (London : Heinemann, 1962)
This story was published serially under the title Marie Curie, my mother ; p. [1].
Includes index.
Jerome P. Webster Library of Plastic Surgery.
Keywords: Curie, Marie, -- 1867-1934.; Biography as Topic